AN ANALYSIS OF MORAL VALUE IN THE MOVIE ENTITLED "SAVING MR.BANKS" BASED ON ITS INTRINSIC VALUE - Mohamad Zaenuri Arif; Asih Kuswandari (PROJECT (Professional Journal of English Education), 2019)
The main objectives of the research entitled An Analysis of Moral Value Reflected in the Movie entitled “Saving Mr. Banks” Based on Its Intrinsic Value are : 1) to understand and find the moral value reflected from the movie, 2) to know the beneficial inputs from analyzing the moral value and intrinsic value of the movie. The research method used in this research is descriptive qualitative method, along with content analysis. The subject of this research is the movie entitled “Saving Mr. Banks” and Screenplay Script of the movie written by Kelly Marcel and Sue Smith. The data were collected, identified, classified, analyzed, and interpreted based on Abram’s theory of intrinsic value. The result of the research : three main moral value found in the movie]: 1) Care, 2) Persistent and never give up, 3) Keeping promise and trustworthy. The beneficial input of analyzing the movie is 1) the synopsis of the movie can be use as instructional media for teaching English 2) by watching the movie, students and teacher can improve their abilities to listen, read, speak, and writing English